Southeast Asia in the new international era - Dayley, Robert (New York ; Abingdon, Oxon : Routledge, 2024)
"This newly revised and updated ninth edition of Southeast Asia in the New International Era provides readers with contemporary coverage of a vibrant region home to more than 675 million people. Sensitive to historical legacies and paying special attention to developments since the end of the Cold War, this book highlights the events, players, and institutions that shape the region politically and economically. The scope of analysis provides context-specific treatment of the region's eleven countries: Thailand, Myanmar (Burma), Vietnam, Cambodia, Laos, Philippines, Indonesia, Timor-Leste, Malaysia, Singapore, and Brunei. Three thematic chapters consider broader regional issues: Southeast Asia Political Economy, ASEAN, and South China Sea. Fully updated, the book's revised content includes new discussion of the effects of the Covid-19 pandemic, Myanmar's 2021 military coup, the return of the Marcos clan in the Philippines, political dynasty in Cambodia, youth demonstrations calling for monarchy reform in Thailand, Malaysia's 2022 elections, and the relocation of Indonesia's capital from sinking Jakarta to Borneo. New to this edition is a dedicated chapter explaining the territorial disputes in the South China Sea. An excellent resource for students and professionals seeking to understand Southeast Asia, this book helps makes sense of the region's political complexity while building a solid foundation for further study"--
Introduction: Southeast Asia Political Economy -- Thailand -- Myanmar (Burma) -- Vietnam -- Cambodia -- Laos -- The Philippines -- Indonesia -- Timor-Leste -- Malaysia -- Singapore -- Brunei -- ASEAN -- South China Sea.
Keywords: Southeast Asia -- Politics and government -- 1945-; Southeast Asia -- Politics and government -- 21st century; Southeast Asia -- Foreign relations; Southeast Asia -- Economic conditions -- 21st century